Kinetic Study of Grafting Acrylamide onto Poly(ethylene terephthalate) Fibres - Celik, Meltem; Pulat, Emsal (Asian Journal of Chemistry, 2010)
Graft copolymerization of acrylamide onto poly(ethylene terephthalate) fibres was carried out in benzyl alcohol medium using hydrogen peroxide as an initiator. Percent graft yield and rate of grafting were determined. The rate of grafting was found to be proportional to 0.64 and 1.11 powers of initiator and monomer concentrations, respectively. The energy of activation value was calculated as 34.3 kJ/mol by carrying out the graft copolymerization reaction at three different temperatures ranging from 70 to 95ºC. The overall rate constants were also determined.